Predicting efficacies of anticancer drugs using single cell HaloChip assay. Issue 8 (14th March 2016) - Ma, Liyuan; Xun, Xiaojie; Qiao, Yong; An, Jincui; Su, Ming
Abstract : Single cell HaloChip assay can be used to assess DNA repair ability. Abstract : Single cell halo assay (HaloChip) is used to quantify DNA repair ability and predict the efficacy of anticancer drugs. After exposure to drugs, cells are patterned onto a substrate to form an ordered single cell array, then embedded inside an agarose gel, and fluorescently stained to generate a characteristic halo surrounding each cell. The extent of DNA repair is quantified by using a relative nuclear diffusion factor (rNDF) derived from the surface areas of nuclei and halos. Several repair-competent and repair-deficient cell lines have been used to validate this method. Drug-inhibitor combinations are also tested in the context of synthetic lethality of chemotherapy, where the use of a repair inhibitor potentiates the effects of DNA damaging agents. This paper highlights the important role of HaloChip in quantifying DNA repair ability, which provides the diagnostic utility to enhance the efficacies of anticancer drugs.